Accumulation and dynamics of manganese in raspberry - Senad MURTIĆ; Emir ŠAHINOVIĆ; Hamdija ČIVIĆ; Emina SIJAHOVIĆ (Acta Agriculturae Slovenica, 2019)
The aim of this study was to evaluate the dynamics of Mn in ‘soil - raspberry’ system on the area around the manganese ore deposits Radostovo in Bužim municipality. Atomic absorption spectroscopy was used to determine the concentration of Mn in soil and plant samples. Fe, Zn and Cu concentration in soil and raspberry plants was also subject of analysis, since these elements have antagonistic relationship with Mn in soils. The concentration of available Mn in soils was low, although the total Mn in the same soils exceeded the Mn toxic values noted in the scientific literature. The chemical and physical properties of the examined soils characterized by a relatively high pH value and good ability to store root-zone air certainly contributed to the decreasing release of available Mn2+ from manganese oxides in soils as well as Mn2+ oxidation to insoluble Mn3+ or Mn4+ ions, resulting in low uptake of Mn by plant roots. The results of study also showed that the absorbed Mn mostly accumulates in leaves and roots of raspberry, and much less in the stem and fruits. That rule in Mn distribution within raspberry plant is in fact identical to all food crops.